Preparation of brookite-type TiO2/Carbon nanocomposite electrodes for application to Li ion batteries - Lee, Du-Hee; Park, Jae-Gwan; Choi, Kyoung Jin; Choi, Heon-Jin; Kim, Dong-Wan (WILEY-V C H VERLAG GMBH, 2008)
The increasing demand for portable energy has generated significant research interest in nanostructured electrode materials, because of their large interfacial contact area with the electrolyte and short path lengths for Li ion transport. To date, titanium dioxide (TiO2) has been widely investigated as an electroactive, Li-insertion host. However, the lithium reactivity of brookite-type TiO2 has rarely been addressed compared to the common polymorphs, anatase and rutile, because of the difficulties encountered in obtaining a phase-pure brookite structure. Herein, we report on the simple synthesis of nanocrystalline brookite-type TiO2 using titanium trichloride (TiCl3) and urea [(NH2)(2)CO]. The average size of the particles precipitated at 100 degrees C was ca. 10 nm. The brookite structure was stable up to 500 degrees C and was completely transformed to the rutile structure at 900 degrees C in an O-2 atmosphere. We evaluated the electrochemical properties of each TiO2 powder heat-treated sample at a preset temperature. Hybrid carbon/TiO2 nanocomposites with high conductivity were also fabricated using a stable suspension of multiwalled carbon nanotubes (MWCNTs) in aqueous suspension with an appropriate surfactant and subsequent precipitation of TiO2. The carbon incorporation clearly improved the capacity retention of TiO2 upon cycling. ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008).
Keywords: RECHARGEABLE LITHIUM BATTERIES; TIO2 ANATASE; NEGATIVE ELECTRODES; CARBON NANOTUBES; INTERCALATION; NANOWIRES; PERFORMANCE; HYDROLYSIS; NANORODS; RUTILE